A comparison between qualitative pilots\' opinion and quantitative flight data on potential loss of control in flight conditions - Macedo, João Paulo Costa Antunes de (2021)
Loss of Control in Flight (LOC-I) is the most lethal type of air accidents in recent aviation history; however, its characteristics are still not well understood, especially from the perspective of the human pilot. This research analysed whether (and to which extent) a quantitative LOC-I detection criterion correlates with subjective pilots\' opinions on the controllability of an aircraft. Six flight test pilots flew a Boeing 777 in four scenarios (different combinations of typical LOC-I precursors) in a flight simulator, and performed 13 manoeuvres specifically designed to assess different aspects of controllability. The aircraft controllability category was determined from the pilots\' qualitative opinions for each manoeuvre, via the so-called Cooper-Harper Rating Scale (CHR), and from recorded flight data, according to the Quantitative Loss of Control Criteria (QLC). Statistical correlation tests determined the degree of correlation between the approaches. A positive weak statistically significant correlation was found between the controllability categories resulting from both CHRs and QLC, thus revealing a lack of clear connection between the understandings of a LOC-I by human pilots and quantitative engineering metrics. The outcomes suggest LOC-I detection criteria should be revised towards including qualitative pilots\' opinion, i.e., human-related factors must be given proper attention prior to the introduction and spread of potential \"LOC-I solutions\" solely based on quantitative metrics.